Performance evaluation of vector evaluated gravitational search algorithm II - Muhammad, B.; Ibrahim, Z.; Ghazali, K.H.; Ghazali, M.R.; Mubin, M.; Mokhtar, M. (2014)
This paper presents a performance evaluation of a novel Vector Evaluated Gravitational Search Algorithm II (VEGSAII) for multi-objective optimization problems. The VEGSAII algorithm uses a number of populations of particles. In particular, a population of particles corresponds to one objective function to be minimized or maximized. Simultaneous minimization or maximization of every objective function is realized by exchanging a variable between populations. The results shows that the VEGSA is outperformed by other multi-objective optimization algorithms and further enhancements are needed before it can be employed in any application.